The Effect Of Skills And Job Satisfaction On Improving Employee's Performance At Pt. Laras Prima Sakti Of Seluma Regency - Lisa Dwi Lestari; Tito Irwanto; Lydia Gustina Putri (Penerbit Jurnal Indonesia, 2023)
human resource planning, which in essence is focused on certain steps taken by management and carrying out work according to their capabilities with the goal of working results that are in line with expectations. by the company. This study aims to determine the effect of skills and job satisfaction on improving employee’s performance at PT. Laras Prima Sakti of Seluma Regency. PT Laras Prima Sakti in West Seluma Sub-District of Seluma Regency is a company operating in the oil palm plantation sector. Based on the research characteristics, a research sample of 52 respondents was obtained using the total sampling method. This type of research is descriptive research with a quantitative approach by distributing questionnaires. The research results showed that skill had a positive and significant effect on employee’s performance at PT. Laras Prima Sakti of Seluma Regency, job satisfaction has a positive and significant effect on employee’s performance at PT. Laras Prima Sakti of Seluma Regency, skill (X1) and job satisfaction (X2) simultaneously have a positive and significant effect on the employee’s performance at PT. Laras Prima Sakti of Seluma Regency. Based on the results of the coefficient of determination test (R2), the variables of expertise (X1) and job satisfaction (X2) contribute to the effect on employee’s performance (Y) at PT. Laras Prima Sakti Seluma